Diagnostic Test Equivalent Hemoglobin Reticulocyte in Iron Deficiency Anemia - Arundina Sanyoto; Ketut Suega; Losen Adnyana; I Made Bakta (Indonesian Biomedical Journal, 2017)
BACKGROUND: Diagnosing iron deficiency anemia (IDA) is easy, but also can be complicated in condition with inflammation. A new modality for diagnostic which isn’t influenced with inflammation is needed. The aim of this study is to find the cut-off point and evaluate the accuracy of reticulocyte hemoglobin equivalent (Ret-He) to diagnose IDA using ferritin as the gold standard.